Glycolic acid-g-chitosan-Pt-Fe3O4 nanoparticles nanohybrid scaffold for tissue engineering and drug delivery - Kumari, Sangeeta; Singh, Raj Pal (International Journal of Biological Macromolecules, 2012)
This work presents the potential use of novel nanohybrid based on chitosan-g-glycolic acid and Pt-Fe3O4 composite nanoparticles in drug delivery and tissue engineering applications. The Pt-Fe3O4 hybrid nanoparticles are prepared by thermal decomposition of H2PtCl6 center dot 6H(2)O at high temperature. The prepared nanoparticles were characterized by transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and physical property measurement system (PPMS). Next step of this paper reveals the potential use of novel hybrids of chitosan-g-glycolic acid and Pt-Fe3O4 hybrid nanoparticles in controlled drug delivery applications. The drug loaded nanohybrid scaffold is prepared by freeze drying of grafted polymer solution. Drug loading and grafting of chitosan was characterized by Fourier transform infrared spectroscopy (FTIR). The cell proliferation also shows that the prepared nanohybrids are biocompatible. The nanohybrid was found to be stable regardless of pH of the medium. Therefore, Pt-Fe3O4 hybrid nanoparticles are viable additive for sustained drug delivery and it could be applied in the field of biomedical. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Cell viability; Chitosan; drug delivery; Glycolic acid grafting; Pt-Fe3O4 hybrid nanoparticle